Weź twego syna, którego miłujesz, idź i złóż go w ofierze! „Związanie" Izaaka w literaturze i myśli rabinicznej - Kalimi, Isaac (Poznańskie Studia Teologiczne, 2010)
The Aqedah story is a crown jewel of the biblical literature. Highlighting genuine emotions and important theological and ethical problems, it holds ground in all monotheistic religions. It brings about several questions concerning the mutual relationship between man and God, and man’s relationship with his son, wife and surroundings. Rabbinic literature provides plurality of perspectives on the Aqedah. It fills in gaps of the narrative and suggests directions o f interpretation that reflects in Josephus and perhaps in the Qumranic literature. Some interpretations are rooted in Apocrypha and Pseudepigrapha literature, and many continue in the medieval Jewish interpretation. Usually the rabbis see God’s request as a test of Abraham’s unconditional belief. Some view the text as Abraham mistaking God’s intent. Others are justifying the placement of God and blaming Satan and Abraham. Several rabbis considered the Aqedah as an act of Kiddush Hashem (martyrdom). Abraham is viewed as one who is truly motivated by his religious belief over moral command, and his immediate acceptance of the command was praised. Many consider the Aqedah also as Isaac’s test. There are several approaches regarding what truly happened on the mount. However, Isaac’s blood cannot be viewed as a counterblast to Jesus’ blood. Sarah’s death was related with the Aqedah. Abraham’s act is considered to be an enduring eminence of Israel.